The effectiveness of IDEA learning model in mathematics concept understanding - Sunismi Sunismi; Yayan Eryk Setiawan (Journal of Education and Learning (EduLearn), 2022)
This research aimed to determine the effectiveness of the issue, discussion, establishment, and application (IDEA) learning model in embedding mathematical concepts understanding. It is a quantitative study with a quasi- experimental approach. This research was conducted at Malang Islamic University with students majoring Mathematics education study program and in their first academic year as the subjects. Subjects were divided into two group, experimental and control and measured their result using posttest only control group design. There are six instruments consisting six items used to measure mathematical concepts understanding. The results confirmed that H0 is rejected, while Ha is accepted proved by t count (3.132) more than  table (1.674). It means there is a significant difference between the of both groups (experimental and control). In addition, the results indicated that the IDEA learning models is effective to assist students in understanding mathematical concepts showed by the higher score of experimental groups than control group. Three factors are involved in order to implement the IDEA learning model effectively; namely: individual problem-solving opportunities, active student involvement, and guidance and assistance (from lecturer) on the IDEA learning model. This research is only limited to preservice teacher, further research is required in order to implement this model for mathematics learning at junior and senior high schools’ level.